Batik Ecoprint Daun Kelengkeng Sebagai Inovasi Desain Produk di Desa Wisata Simoketawang Kec Wonoayu Kabupaten Sidoarjo - Yulyar Kartika Wijayanti; Kharisma Sintyas Syaharani; Febby Rahmatullah Masruchin; Riska Amelia; Vika Amalia Fahmi; Erna Melinda; Enjelina Novitasari (Universitas Nahdlatul Ulama Surabaya, 2022)
Matching fund is the program that helps starting the business women in PKK to increase their economicproductivity. The University of 17 Agustus 1945 or Untag Surabaya through the Matching Fundprogram seeks to connect the world through business world in simoketawang village. It makes realefforts to equip new business in preparing the women in PKK organization to enter the business worldso as to help them set up new business. We will set up new business dealing with longan’s leaves /daunklengkeng. We have trained them in making the products, innovation and design and also given newideas in their economic productivity so that they become reliable business women in the ecoprint batikbusiness. The matching fund activities is to improve the quality of human resources for PKK women throughecoprint batik product in longan’s Tourism Simoketawang Village, Wonoayu District, Sidoarjo Regency.The method of implementing this activity is carried out collaboratively between the Matching Fundprogram implementers, the Community Empowerment & Village Development Agency, and is dividedinto three stages, namely, preliminary surveys, training and marketing with the target of women of PKKorganization Asman Kelasi. The results of the activities include an increase in practical knowledge thatis easy to apply in production for ecoprint batik making and also the business. In this training womenparticipants know how to make ecoprint batik with special longan leaves and also plan the marketing.Women partners in PKK showed great enthusiasm and enthusiasm in supporting the program in longantourism village and participated in this training we can see by the success of product marketing afterthey make their products exhibition in their village.